THE ROLE OF USING AUTHENTIC MATERIALS IN FORMATIVE ASSESSMENT WHILE TEACHING ENGLISH - Ismailova Roziya Bahodir qizi, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This thesis explores the effectiveness of using authentic materials—specifically podcasts from BBC World Service—to enhance the extensive and interactive listening skills of upper-intermediate first-year journalism students at the Uzbek State World Languages University. The study emphasizes the pedagogical benefits of integrating content-based listening activities, vocabulary acquisition, and role-play to improve students’ comprehension, pronunciation, and communicative competence in English for Occupational Purposes (EOP). Grounded in theories of materials development (Macalister, 2016; Maftoon et al., 2016; Timmis, 2016), the designed lesson demonstrates how authentic input, learner engagement, and task-based instruction contribute to meaningful language learning outcomes